Clinical Improvement after Surgical Debridement and Synovectomy on 4 Year Old Girl with Chronic Septic Arthritis of the Hip - Utomo, Pamudji; Adriansyah, Denny (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Incidence of septic arthritis in children less than 5 years old about 5 from 100,000 cases every year and adult above 64 years old about 8.4 cases every 100,000 people every year. The diagnosis of the chronic septic arthritis, especially in hip joint is still challenging, even for skilled doctor in musculoskeletal. Delayed diagnosis and inadequate treatment can lead to permanent joint damage and impairment.Case presentation: In this case we discuss about clinical improvement of chronic septic arthritis in a 4 year old girl with hip pain that had been felt since 2 months before admission. Physical examination, laboratory examination, and ultrasonography examination was done and the diagnosis had been made.Results: A surgical debridement and synovectomy was done with addition antibiotic therapy. The patient not only felt the pain was relieved but also can return into good function of hip joint.Conclusion: Diagnosis with proper early treatment is expected to reduce permanent joint loss and improve the clinical outcome for the patient.Keywords: septic arthritis, hip, synovectomy, surgical debridementCorrespondence: Pamudji Utomo. Prof DR R Soeharso Orthopaedic Hospital, Pabelan, Kartasura, Surakarta, Central Java. Email: scapoid@yahoo.com.Indonesian Journal of Medicine (2020), 05(03): 253-258https://doi.org/10.26911/theijmed.2020.05.03.11